Seasonal variation in the international normalized ratio of neonates and its relationship with ambient temperature. Issue 1 (December 2016) - Iijima, Shigeo; Sekii, Katsuyuki; Baba, Toru; Ueno, Daizo; Ohishi, Akira
Abstract Background The morbidity and mortality rates due to cardiovascular events such as myocardial infarction are known to exhibit seasonal variations. Moreover, changes in the ambient temperature are reportedly associated with an increase in these events, which may potentially involve blood coagulation markers. Bleeding due to vitamin K deficiency in neonates, which is associated with high mortality and a high frequency of neurological sequelae, is more commonly observed during the summer season and in warm regions in Japan. To determine the presence of seasonal variation and the influence of ambient temperature on blood coagulation markers in healthy term neonates, we assessed the international normalized ratio (INR) values measured using CoaguChek XS. Methods We studied 488 consecutive healthy term neonates who were born at a perinatal center between July 2012 and June 2013. The INR values were measured using CoaguChek XS in 4-day-old neonates who received nursing care in the newborn nursery throughout the duration of hospitalization. The seasonal variations in the INR values and environmental effects on the INR were assessed. Results The mean monthly INR values peaked in July (1.13 ± 0.08), whereas the lowest values were observed in January (1.05 ± 0.08). Higher levels of INR were observed during the summer season (June to August) than during the winter season (December to February). Simple linear regression analysis indicated the presence of weakly positive but significant correlations between INR and outdoor temperature (r = 0.25, p < 0.001), outdoor relative humidity (r = 0.19, p < 0.001), and room relative humidity (r = 0.24, p < 0.001), and the presence of a significant negative correlation between INR and room temperature (r = −0.13, p = 0.02). Furthermore, multiple linear regression analysis showed that only outdoor temperature significantly influenced the INR. Conclusions A seasonal variation in the INR values was observed among neonates, possibly due to the variation in ambient temperature. Even though the neonates received nursing care in the newborn nursery that was constantly air-conditioned, the outdoor temperature was the most influential factor on INR.